The training of Penny Heyns of South Africa Olympic gold medalist in breaststroke - Bidrman, J. (American Swimming ASCA Newsletter)
The coach of Penny Heyns some background, and then he tries to explain how he plans the season, and he will talk about each season in a separate manner. Further on he wants to give a little bit of an idea how Penny evolved and what kind of a relationship she and the coach got. Briefly he will discuss weight training and show some of her dryland drills. At the end, the coach will offer some subjective comments and tell the reader why he thinks Penny won the Olympics.